Penggunaan Media Youtube dalam Pembelajaran PAI di Sekolah - Elgi Septrio Neldi; Gufra Ifnaldi; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the use of YouTube in Islamic Religious Education (IRE) learning in schools. The results indicate that the use of YouTube enhances students' interest, facilitates the understanding of abstract material, and develops critical thinking and digital skills. Videos presented through YouTube help students understand IRE content in a more engaging and practical way, particularly in matters of theology, worship practices, and Islamic history. Despite the many benefits, the use of YouTube also faces challenges such as the selection of appropriate content, limitations in technological infrastructure, risk of distractions, and more complex time management. Therefore, strict supervision, careful content selection, and effective classroom management by teachers are necessary to optimize the use of YouTube in IRE learning. This study recommends the proper integration of YouTube into the learning process, supported by improved infrastructure and teacher training.